A zinc, copper and citric acid biocomplex shows promise for control of Xylella fastidiosa subsp. pauca in olive trees in Apulia region (southern Italy) - SCORTICHINI, Marco; CHEN, Jianchi; DE CAROLI, Monica; DALESSANDRO, Giuseppe; PUCCI, Nicoletta; MODESTI, Vanessa; L’AURORA, Alessia; PETRICCIONE, Milena; ZAMPELLA, Luigi; MASTROBUONI, Francesco; et al. (Phytopathologia Mediterranea, 2018)
The bacterium Xylella fastidiosa subsp. pauca is associated with the “olive quick decline syndrome” in the Apulia region of southern Italy. To investigate control of this phytopathogen, a compound containing zinc and copper complexed with citric-acid hydracids (Dentamet®) was evaluated for in vitro and in planta bactericidal activity. Confocal laser scanning microscopy, fluorescent quantification and atomic emission spectroscopy were then used to determine if the compound reached the xylem networks of leaves, twigs and branches of olive, to release zinc and copper within the xylem. A 3-year field trial in an olive orchard containing mature Cellina di Nardò and Ogliarola salentina olive trees, and officially declared infected by X. fastidiosa subsp. pauca,was also carried out o to determine if the compound affected severity of the disease. Each year, from early April to October (excluding July and August), six spray treatments of 0.5% (v:v) Dentamet® were applied on the olive tree crowns. The compound reduced severity of symptoms in both cultivars. Most untreated trees died by the end of the trial, whereas all treated trees survived with good vegetative status as assessed by a normalized difference vegetation index. Quantitative real-time PCR was performed from June 2016 to September 2017, following the official procedures established by the European and Mediterranean Plant Protection Organization. The analysis revealed a statistically significant reduction of X. fastidiosa cell densities within the leaves of treated trees. These promising results suggest that integrated management to reduce severity of X. fastidiosa that includes regular pruning and soil harrowing with spring and summer spray treatments with Dentamet®, is likely to effectively control the disease.